2023
DOI: 10.3390/ph16121641
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Formation of Ternary Inclusion Complex of Pterostilbene

Yousef A. Bin Jardan,
Abdul Ahad,
Mohammad Raish
et al.

Abstract: Pterostilbene (PTS) is a naturally occurring phytoalexin. PTS displays limited water solubility, which consequently results in its diminished oral bioavailability. Therefore, a ternary inclusion complex (TIC) of PTS with β-cyclodextrin (βCD) in the presence of ternary substance Pluronic® F-127 (PLF) was prepared using microwave technology. The PTS-TIC was characterized by dissolution performance. Further, the prepared TIC was characterized by DSC, FTIR, NMR, XRD, and SEM analysis. Additionally, the antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The findings of our DSC studies are also confirmed by literature data provided by FTIR analyses investigating the spectra of either the pure substances or their combinations [67][68][69][70]. For example, FTIR analysis of pure P407 showed absorption bands at 3000-2850 cm −1 , -CH 2 stretch corresponding to the bonds present in PEO and PPO blocks, and stretching vibrations of C-C bonds at 1100 cm −1 and at 1380 cm −1 due to the symmetric angular deformation of CH 3 [67].…”
Section: Of 32supporting
confidence: 87%
See 1 more Smart Citation
“…The findings of our DSC studies are also confirmed by literature data provided by FTIR analyses investigating the spectra of either the pure substances or their combinations [67][68][69][70]. For example, FTIR analysis of pure P407 showed absorption bands at 3000-2850 cm −1 , -CH 2 stretch corresponding to the bonds present in PEO and PPO blocks, and stretching vibrations of C-C bonds at 1100 cm −1 and at 1380 cm −1 due to the symmetric angular deformation of CH 3 [67].…”
Section: Of 32supporting
confidence: 87%
“…This observation led to the inference that P407 engages with the hydrophobic cavity of HPβCD. Also, Bin Jardan et al [69] used FTIR analysis to identify the interactions developed between the materials of their ternary inclusion complex (comprising a pterostilbene, β-CD, and P407). Indeed, they proved that the combination of the materials diminished the peaks' intensities and caused displacements of peaks compared to those of pure compounds.…”
Section: Of 32mentioning
confidence: 99%
“…To address this challenge, researchers have explored various methods. These approaches include the development of amorphous solid dispersion [ 23 ], inclusion complex [ 24 , 25 ], nanoparticles [ 26 ], cocrystals [ 27 , 28 , 29 ], and the production of nanoemulsions [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, PTR complexed with HPβCD exhibits potent antibacterial effects against Fusobacterium nucleatum , a key periodontal pathogen. Additionally, its antimicrobial and immunomodulatory properties make PTR a promising candidate for nutraceutical use in the adjunctive treatment of periodontitis [ 24 , 25 ]. Nanoparticles of PTR obtained by Zhao et al successfully decreased blood glucose levels, enhanced antioxidant capacity, and reversed micro-inflammation in mice [ 26 ].…”
Section: Introductionmentioning
confidence: 99%